Identity, Flexibility and Sustainability for the new Social Housing - Sposito, Cesare (TECHNE - Journal of Technology for Architecture and Environment, 2012)
Pubblica (lit. Public Residential Construction), undergone over the last sixty years in Italy, have brought about new lines of thought with regard to places to live. The high cost of renewal and re-functionalization of the E.R.P. areas, the absence of services, which have transformed them into dormitory suburbs, have led us to rethink new urban environments as places possessing a sense of identity, in which to provide communal services and spaces for neighborly relations. Moreover, the social, economic and political dynamics of the last few years have modified not only life styles, but also the typology of householder, ever more sensitive to the quality of product and environmental issues. This contribution discusses several principles as a point of departure for a new Social Housing.